Unusual case of a right atrial inflammatory myofibroblastic tumor presenting with an episodic cyanosis in an infant. Issue 9 (21st June 2022) - Zhou, Xiang; Song, Laichun; Cheng, Youping; He, Chunli; He, Jiahui; Han, Xiao
Abstract: Cardiac inflammatory myofibroblastic tumor (IMT) is a rare benign tumor that occurs mainly in infants and children. We report a case of right atrial IMT in a 1‐month‐old girl with episodic cyanosis. Both echocardiography and cardiac computed tomography revealed a right atrial mass. The patient underwent a complete surgical resection of the mass and the postoperative histological examination confirmed the diagnosis of cardiac IMT. The patient recovered well after the operation and further follow‐up evaluation was uneventful.